Impact of the COVID-19 lockdown on air quality in the Delhi Metropolitan Region. (March 2021) - Roy, Shouraseni Sen; Balling, Robert C.
Abstract: With the rapid spread of COVID-19 related cases globally, national governments took different lockdown approaches to limit the spread of the virus. Among them, the Government of India imposed a complete nationwide lockdown starting on March 25, 2020. This presented a unique opportunity to explore how a complete standstill in regular daily activities might impact the local environment. In this study, we have analyzed the change in the air quality levels stemming from the reduced anthropogenic activities in one of the most polluted cities in the world, the Delhi Metropolitan Region (DMR). We analyzed station-level changes in particulate matter, PM10 and PM2.5, across the DMR between April 2019 and 2020. The results of our study showed widespread reduction in the levels of both pollutants, with substantial spatial variations. The largest decreases in particulate matter were associated with industrial and commercial areas. Highest levels of PM10 and PM2.5 were observed near sunrise with little change in the time of maximum between 2019 and 2020. The results of our study highlight the role of anthropogenic activities on the air quality at the local level. Highlights: There was substantial decline in the levels of PM10 (20 to 70%) and PM2.5 (15 to 90%) in air quality across the DMR. The highest decline was observed over the downtown core area and the adjacent industrial areas in the east and west. Areas experiencing greater decline are associated with greater proportion of commercial land uses and economic activity. Overall, the decline in PM10 was more widespread than PM2.5 . The diurnal patterns of peak time for average monthly levels occurred at midnight for PM10 and early morning for PM2.5 . The time of maximum values did not change significantly between 2019 and 2020